Exploration of Orchids and Ferns on the Aik Berik Hiking Trail in Mount Rinjani National Park - Pazira, Ayun; Zulkifli, Lalu; Raksun, Ahmad; Mertha, I Gde (Jurnal Biologi Tropis, 2026)
Indonesia is recognized as a country rich in biodiversity, boasting an extensive variety of plants and animals. Lombok Island, one of Indonesia's islands, showcases a significant level of biodiversity. This island is home to the Mount Rinjani National Park. Within the TNGR region, Aik Berik Village serves as the designated hiking route for Mount Rinjani National Park, featuring a remarkable variety of plant life, such as orchids and ferns. Nonetheless, studies exploring the orchids and ferns along the Aik Berik hiking path remain scarce, and no one has examined them across different elevations, making this research essential. This study aims to determine the types of orchids and ferns and their distribution on the Aik Berik hiking trail of Mount Rinjani National Park. The method used in this study is the cruise method. The findings of this research identified 14 genera and 24 species of orchids, which include 17 epiphytic orchids and 7 terrestrial orchids, totaling 940 individuals. The orchid with the broadest distribution is Pinalia multiflora, located at altitudes between 1,000 and 2,500 meters above sea level, with a count of 100 individuals. Conversely, the least common species is Dendrobium rindjaniense, which exists at heights of 2,000 to 2,500 meters above sea level, totaling only 5 individuals. The study also discovered 15 families, 22 genera, and 31 species of ferns, comprising 25 terrestrial ferns and 6 epiphytic ferns, amounting to 8,165 individuals in total. The fern species that is distributed the most is Macrothelypteris torresiana, found at altitudes of 1,000 to 2,500 meters above sea level, with 1,150 individuals recorded. In contrast, the species with the least distribution is Huperzia selago, which appears at altitudes between 1,000 and 2,000 meters above sea level, with just 20 individuals present.